Making up the planned initial cost of finishrd products at OJSC “BSW – Management Company of Holding “BMС” by means of the SAP ERP system controlling module - A. V. Potapenko; S. N. Astratov; I. I. Lavrish (Литьë и металлургия)
The article reveals the process of making up the planned initial cost of finished products and detailing indirect costs on the long‑range production example by means of the “Controlling” module of the SAP ERP system. The problems of displaying indirect costs for product that practically do not depend on the quantity of products produced, and calculating direct costs through a specification mechanism based on a basic material records reference book have been solved. As a solution, the key settings implementation in the system configuration and the set of planning interface programs implementation developed in the ABAP/4 programming language were used.